(untitled) (International Journal of Mathematics and Physics, 2021)
In the article, the authors present experimental data on the specific power equivalent dose (EDR) of radiation gamma, beta, and alpha radiation in samples containing copper, zinc and lead of pyrite-polymetallic ores, which were mined at the Zhezkent mining and processing plant (The East Kazakhstan region, Borodulikhinsky district). The measurements were carried out by dosimeters and radiometers "RKS-01-SOLO" with alpha, beta and gamma scintillation detectors. For ores, the dependences of the specific power of the equivalent dose of gamma radiation on the content of various concentrations of copper, zinc and lead were revealed. The analysis of natural decay chains, the daughter products of which are stable isotopes of copper and zinc, is carried out. A relationship has been proposed between the concentrations of nickel, copper, lead and EDR, which gives prospects for further spectrometric studies of these samples to identify the corresponding lines of accompanying gamma radiation during decays of radionuclides contained in the samples under study and radiation conversion of stable isotopes. The results of this work will make it possible to build a model for studying the radiation of ores, the distribution of natural radionuclides in the earth’s crust, which will undoubtedly provide prerequisites for the verification and clarification of the sources and mechanisms of emanation and coagulation of radon isotopes, which form the natural radiation background of the surface atmospheric layer.